1886 Md. Laws 602, ch. 375 - (:unkn) unknown (General Publisher, 1886)
Prohibited carrying, concealed or openly with intent or purpose of injuring another, any pistol, dirk-knife, Bowie-knife, slung-shot, Billy, sandclub, metal knuckles, razor, or any other dangerous or deadly weapon whatsoever.
--
Keywords: CARRY - INTENT TO COMMIT CRIME